EFFECTIVE TECHNIQUES OF IMPROVING STUDENTS' READING COMPREHENSION (Web of Teachers: Inderscience Research, 2024)
Improving students’ reading comprehension is essential for academic success and lifelong learning. This article explores theoretical framework and a range of effective techniques aimed at enhancing students’ ability to understand, analyze, and retain written information. The review focuses on cognitive strategies, such as summarization, self-questioning, and visualization, which help students actively engage with texts and organize their thoughts. Metacognitive strategies like self-monitoring and prediction also play a critical role in fostering deeper comprehension. Collaborative techniques, including reciprocal teaching and peer discussions, promote social interaction and cognitive processing, leading to improved understanding.